Efficacy and safety of anti-PD-1 and anti-PD-1 combined with anti-CTLA-4 immunotherapy to advanced melanoma: A systematic review and meta-analysis of randomized controlled trials. Issue 26 (June 2017) - Hao, Chunyan; Tian, Jinhui; Liu, Huiling; Li, Fei; Niu, Hongxia; Zhu, Bingdong
Abstract: Background: Anti-PD-1 monoclonal antibodies, nivolumab and pembrolizumab, and anti-CTLA-4 antibody ipilimumab are being in clinic trials to treat melanoma. Here, we performed a meta-analysis to evaluate the efficacy and toxicity of them against advanced melanoma. Methods: Eleven reports from 6 randomized control trials on treating metastatic melanoma, which were divided into 3 subgroups, nivolumab/pembrolizumab versus chemotherapy, nivolumab versus ipilimumab, and nivolumab-plus-ipilimumab versus ipilimumab, were included and the meta-analysis was performed for each subgroup. The outcome measures were objective response rates (ORR), median progression free survival (PFS), 1-year overall survival rates (OS), and toxicity estimated by grade 3 to 4 adverse events. Results: For nivolumab/pembrolizumab versus chemotherapy, nivolumab versus ipilimumab, and nivolumab-plus-ipilimumab versus ipilimumab, the pooled risk ratios (RR) of the ORR were 3.43 (95% CI: 2.57–4.58), 2.51 (95% CI: 2.03–3.09), and 3.28 (95% CI: 2.58–4.17), respectively. The pooled HR of PFS were 0.42 (95% CI: 0.36–0.49), 0.58 (95% CI: 0.50–0.66), and 0.41 (95% CI: 0.30–0.52), respectively. The pooled RR of 1-year OS was 1.37 (95% CI: 1.08–1.74) and 1.54 (95% CI: 0.90–2.63) for nivolumab versus ipilimumab and nivolumab-plus-ipilimumab versus ipilimumab. These results suggested that anti-PD-1 monotherapy and nivolumab-plus-ipilimumab therapy had ORR and PFS benefit compared with the control group. Anti-PD-1 treatment increased 1-year OS for patients compared with ipililumab treatment. But there is no significantly difference on 1-year OS between the nivolumab-plus-ipilimumab treatment and the ipilimumab treatment group. The toxicity analysis showed that there is less risk of adverse events in the anti-PD-1 treatment group compared with the chemotherapy and ipilimumab group. Combining nivolumab with ipilimumab increased the risk for high-grade adverse events compared with ipilimumab alone but the adverse events were generally manageable. Conclusions: Anti-PD-1 monotherapy and nivolumab-plus-ipilimumab therapy improved ORR and prolonged PFS of patients with advanced melanoma and the adverse events are generally manageable. The therapy is indeed a promising approach for treatment of advanced melanoma.